Antioxidant activities and laxative effect of bioactive compounds from Cynara cardunculus var. sylvestris - Tajini, Fatma; Jelassi, Awatef; Hamdani, Amal; Salem, Ali; Abdelhedi, Ola; Ouerghui, Abid; Sebai, Hichem (Penerbit Universiti Kebangsaan Malaysia, 2024)
The present study aims to investigate the antioxidant and anti-constipation activities of the derived phenolic extracts in ribs wild cardoon (Cynara sylvestris). Analysed extracts (acetone, methanol and aqueous) exhibited high level of phenolic compounds and excellent antioxidant activities with significant IC50 values (p≤0.05), as assessed by the DPPH radical-scavenging activity (0.84±0.08 - 2.44±0.007 μg/mL), ABTS cationic radical test (0.96 ±0.01- 136.67±6.75 μg/mL) and β-carotene bleaching assay (2.09±0.02-51.12±1.32 μg/mL). Also, higher levels of insoluble dietary fibers were found (56.18 ± 0.91% DW of neutral detergent fiber). The in vivo investigation was performed on Wistar rats to explore the ability of C. sylvestris aqueous extract (CSAE) in the enhancement of the gastrointestinal transit and the treatment of induced constipation by Loperamide (commercialized as Idium). A significant increase of 15, 24.5 and 32.4% in gastrointestinal motility was recorded when doses of CSAE increased (75, 150 and 300 mg/ kg b.w, respectively). Food intake, water consumption, number and weight of stools were also increased in a dosedependent manner, compared to the positive control (untreated). Moreover, CSAE provided significantly (p≤0.05) and dose-dependently protection against oxidative stress by preserving normal antioxidant enzymes activities (SOD and GPx) in intestinal and colonic mucosa, and resorted hepatic enzymes (AST and ALT) and renal (urea and creatinine) levels to normal values. These results can be explained by the abundance of phenolic compounds and insoluble fibers in this plant. Therefore, its use can be encouraged in alimentary and pharmaceutical applications as antioxidant and laxative food supplements.